Bone-inspired 3D printed structures for construction applications - Naboni, Roberto; Kunic, Anja (Gestão & Tecnologia de Projetos, 2019)
Overconsumption of resources is one of the greatest challenges of our century. The amount of material that is being extracted, harvested and consumed in the last decades is increasing tremendously. Building with new manufacturing technology, such as 3D Printing, is offering new perspectives in the way material is utilized sustainably within a construction. This paper describes a study on how to use Additive Manufacturing to support design logics inspired by the bone microstructure, in order to build materially efficient architecture. A process which entangles computational design methods, testing of 3D printed specimens, developments of prototypes is described. A cellular-based tectonic system with the capacity to vary and adapt to different loading conditions is presented as a viable approach to a material-efficient construction with Additive Manufacturing.